New Plasmid-Borne Antibiotic Resistance Gene Cluster in Pasteurella multocida - Kehrenberg, Corinna (American Society for Microbiology, 2003)
A new antibiotic resistance gene cluster comprising genes for sulfonamide (sul2), streptomycin (strA-strB), and tetracycline [tetR-tet(H)] resistance was detected on plasmid pVM111 from Pasteurella multocida. The tetR-tet(H) gene region was inserted between sul2 and strA, possibly by illegitimate recombination. Two potential recombination sites of 18 and 25 bp were identified.